Antibiotic Resistance and Integron of Vibrio cholerae Detection from School Street Foods in Jakarta - DEASHINTA, NADIA; WATURANGI, DIANA ELIZABETH; YOGIARA, YOGIARA (HAYATI Journal of Biosciences, 2009)
Street foods represent foods and beverages prepared by vendors in streets or other public places, i.e. schools. Food safety issues perceive street foods as a potential major public risk. Street foods contaminated with toxigenic Vibrio cholerae may lead to serious poisoning to school-age children. In this study, 17 isolates of V. cholerae were obtained from nine (45%) of total 20 street foods samples collected in Jakarta. Five (29%) were confirmed to be V. cholerae O1, serotype Ogawa using biochemical tests and serological identification. Of the 17 V. cholerae isolates 47% proved to be resistant to ampicillin, 35% to trimethoprim, 17.6% to tetracycline, and 17.6% to streptomycin. A class 1 integrons bearing streptomycin/spectinomycin resistant gene cassette of aadA1c were discovered on isolate Vc25n. This may leads to horizontal transfer of the antibiotic resistant genes to other bacteria. Key words: foods, Vibrio cholerae, antibiotic resistance, integron